The attitudes of faculty members and students at King Saud University towards the use of micro learning - Al-Qahtani, AlMaha Ali Abdullah; Al-Ateeq, Latifah Khalil (Journal of Curriculum and Teaching Methodology, 2023)
This study was designed to explore the attitudes of Faculty Members and Students of King Saud University Towards the Use of Micro learning. The respondent sample included (190) Faculty Members, and (414) Students from King Saud University, where the descriptive survey approach was used to achieve the objectives of the study and to answer its questions using a customized questionnaire. and The Results Resulted in Positive Trends Among Faculty Members and Students at King Saud University Towards the Importance of Using Microlearning in The Educational Process, And The Existence of Neutral Trends Among Faculty Members and Students at King Saud University Towards The Extent of The Appropriateness of the Use of Microlearning In The Educational Process.